Library spaces for 21st-century learners a planning guide for creating new school library concepts. (Chicago American Association of School Librarians, 2013)
This book focuses on planning contemporary school library spaces with user-based design strategies
First through third editions, published 1977-1987, have title Library management; Fourth through seventh editions, authored by Robert D. Stueart and Barbara B. Moran and published 1993-2007, have title Library and information center management
Includes bibliographical references and index
Keywords: School libraries -- Planning; Electronic books